Javier Huerta Calvo, ed.: La escuela de Astorga (Luis Alberto Luengo, Ricardo Gullón, Leopoldo Panero, Juan Panero). - Díaz Margarit, Carmen (Dicenda. Estudios de lengua y literatura españolas, 1996)
Sin resumen